Modified SnO2-APTES gas sensor for selective ammonia detection at room temperature. (2019) - Hijazi, Mohamad; Rieu, Mathilde; Stambouli, Valérie; Tournier, Guy; Viricelle, Jean-Paul; Pijolat, Christophe
Abstract: The feasibility of room temperature ammonia gas sensors based on tin dioxide (SnO2 ) functionalization has been demonstrated. 3-aminopropyltriethoxysilane (APTES) was used as an intermediate step, followed by functionalization with molecules having acyl chloride with different end functional groups molecules such as alkyl, acid and ester groups. Modified films were characterized by attenuated total reflectance infra-red spectroscopy (ATR-FTIR). Upon exposure to ammonia gas, the electrical conductance of alkyl, acid and ester modified SnO2 -APTES increases, whereas other reducing gases such as ethanol, carbon monoxide and acetone show no change in conductance. Furthermore, ester modified SnO2 is more selective than acid modified sensor regarding ethanol and carbon monoxide gases